Establishing a national biobank. Biobanking infrastructure initiative in Slovakia - Public policy, legal and ethical issues. Issue 1 (March 2020) - Glasa, Jozef; Kollár, Drahomír; Čvapek, Peter; Glasová, Helena; Antošová, Martina; Pella, Daniel; Kvietiková, Ivica
Abstract: Resulting from a multi-stakeholder initiative in 2017, a rapid process is underway in Slovakia with the aim of establishing a national system of biobanks by 2020. A combined top-down and bottom-up approach is being followed under the leadership of the Ministry of Health Institute for Research and Development. Relevant national stakeholders, with international expert partner institutions providing additional know how and networking, have been successfully involved since the very beginning of this initiative. State-of-the-art biobanking facilities are to be built in order to accommodate the Slovak National Biobank in the city of Martin (Central Slovakia) and the other major biobank in the city of Košice (Eastern Slovakia), while existing structures – future local biobanks – will be upgraded to achieve complete technical and logistical compatibility. This should enable full compliance of the Slovakia's biobanking system with the appropriate international ethical, legal and professional standards. A related legislative activity has been started, aimed at a comprehensive updating of the existing Slovak biomedical research and health care legislation, to provide for the necessary legal certainty. After successful completion of the Initiative, the Slovakia's biomedical research infrastructure is to be better set for supporting excellent domestic research and development efforts, as well as for its involvement in high-quality international research collaborations and partnerships.